The Sociolinguistics Perspectives on Gastronomy of Nias Culinary - Afore Tahir Harefa; Wina Anjelina Harefa; Silvan Herniyanti Telaumbanua; Putrawan Saleh Laia (Teaching English and Language Learning English Journal, 2026)
This research looks at how Nias culinary names represent sociolinguistic meanings in the gastronomy of Nias traditional foods. The study examines three issues: (1) how Nias culinary names function as a symbol of identity, (2) how they reflect variation and change in naming practices, and (3) how they transmit cultural knowledge across generations. As a result, the research seeks to explain the sociolinguistic functions encoded in the naming reasoning for Nias food items. Using a qualitative descriptive approach, data were gathered from community explanations of thirteen Nias cuisine names and analyzed using theme coding based on Wardhaugh and Fuller’s (2015) sociolinguistic elements. The findings show that all culinary names use local Li Niha/ Nias name naming, which indicates affiliation and group participation. Several names also exhibit systematic variation and change due to process-based naming patterns, contextual use in adat and hospitality contexts, and minimal evidence of modernity and cross-food comparability. Most artifacts also serve as cultural transmission instruments, conserving intergenerational information regarding preservation techniques, traditional culinary skills, customary etiquette, and historical survival practices. These findings indicate that Nias gastronomy is a linguistic cultural archive in which food naming promotes identification, adapts to social settings, and preserves historical values.